Speech Acts Spoken by the Characters in the Movie Entitled â€œBridge to Terabithiaâ€ - Rustandi, Andi; Rizki, Intani Permata (Pendidikan Bahasa Inggris (Universitas Internasional Batam), 2018)
This research was aimed at identifying the kinds of illocutionary acts spoken by the major and minor characters in the movie, perlocutionary acts performed by the hearers towards the utterances spoken in the movie, and the contextual aspects that influenced the illocutionary and perlocutionary acts indicated in the movie. The qualitative research was applied as the research design and the data were collected through content analysis. The writers employed purposive sampling as their sampling technique. Based on the research findings, the writers identified five kinds of illocutionary acts based on Searle?s theory, namely, representative, directive, commisive, expressive, and declaration. Furthermore, the writers identified 37 perlocutionary acts performed in the movie and the study showed 15 different situational contexts influenced the illocutionary and perlocutionary acts identified in the movie. In short, the kinds of illocutionary act that frequently appears and gives big influence in the movie is a directive illocutionary act.